Potential cytochrome P450-mediated pharmacokinetic interactions between herbs, food, and dietary supplements and cancer treatments. (October 2021) - Gougis, Paul; Hilmi, Marc; Geraud, Arthur; Mir, Olivier; Funck-Brentano, Christian
Graphical abstract: Highlights: Herbs food and dietary supplements (HFDS) could modify cytochromes' activity. Most anticancer drugs are metabolised by cytochromes. Pharmacokinetic interactions via cytochromes could be predicted. An easy-to-read table has been generated to cross and anticipate HFDS-drug interactions. Abstract: Herbs, food and dietary supplements (HFDS), can interact significantly with anticancer drug treatments via cytochrome p450 isoforms (CYP) CYP3A4, CYP2D6, CYP1A2, and CYP2C8. The objective of this review was to assess the influence of HFDS compounds on these cytochromes. Interactions with CYP activities were searched for 189 herbs and food products, 72 dietary supplements in Web of Knowledge® databases. Analyses were made from 140 of 3125 clinical trials and 236 of 3374 in vitro, animal model studies or case reports. 18 trials were found to report direct interactions between 9 HFDS with 8 anticancer drugs. 21 HFDS were found to interact with CYP3A4, a major metabolic pathway for many anticancer drugs. All 261 HFDS were classified for their interaction with the main cytochromes P450 involved in the metabolism of anticancer drugs. We provided an easy-to-use colour-coded table to easily match potential interactions between 261 HFDS and 117 anticancer drugs.